Muzzled eaudiobook - Rosenfelt, David (Andy Carpenter, 2020)
"Narrator Grover Gardner returns to breathe life into listeners' favorite dog-loving lawyer...In his vivid portrayal of the wisecracking Andy, Gardner creates a sense of a cheerful reunion with the lawyer for longtime listeners and a warm greeting for newcomers." — AudioFile Magazine, Earphones Award winner In David Rosenfelt's Andy Carpenter mystery, Muzzled , Andy and his beloved golden retriever, Tara, are back on the case as a favor to a friend. Andy Carpenter is a lawyer who would rather not practice law. He'd rather spend his time working with the Tara Foundation, his dog rescue organization, and being with his family and his two dogs, Tara and Sebastian. But when a friend asks him for a favor that involves both dogs and his lawyerly expertise, he can't say no. Andy's friend Beth has found a stray that seems to have belonged to a murder victim—in fact, the man and two of his colleagues died in an explosion a few weeks ago. But when the murdered man contacts Beth, asking for his dog back, Andy knows there must be more to the story. The man claims his life is in danger, and that's why he disappeared. As much as Andy doesn't want to get involved—anything to avoid a new case—he can't help but come to the rescue of a man who'd risk everything, even his life, to reunite with his dog. Once again, David Rosenfelt delivers suspense and laughter in equal measure in another engaging mystery from "one of the most unforgettable voices in the genre." (Associated Press) A Macmillan Audio production from Minotaur Books Praise for Grover Gardner as Andy Carpenter: "Listening to Grover Gardner narrating a David Rosenfelt novel is like sliding into favorite slippers at the end of a long day: One feels the joyful gratification of a perfect fit."— AudioFile Magazine on Bark of Night "Grover Gardner's narration of Rosenfelt's whodunits is what good audiobooks are all about...Gardner's delightful portrayal of defense lawyer Andy Carpenter continues to be fresh, allowing listeners to glimpse Andy's soft heart and quick humor."— AudioFile Magazine on Outfoxed